2006
DOI: 10.1007/s00213-006-0453-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the 5-HT2C receptor antagonist SB242084 on locomotor activity induced by selective, or mixed, indirect serotonergic and dopaminergic agonists

Abstract: SB242084 potentiated the locomotor stimulant effects of both indirect DA and 5-HT agonists. This potentiation may reflect two distinct mechanisms. The first involves direct enhancement of DA activity as shown by potentiation of the effects of amphetamine and methylphenidate. The second mechanism reflects an unmasking of stimulatory 5-HT receptors activated by 5-HT releasers (possibly 5-HT(1B/2A)) through blockade of inhibitory 5-HT(2C) receptors. The failure of SB242084 to potentiate the effect of citalopram m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 63 publications
5
69
0
Order By: Relevance
“…Indeed, considering that the stimulant and reinforcing effects of cocaine depend in large part on elevated DA activity in the NAc (Di Chiara, 2002;Dunnett and Robbins, 1992), 5-HT 2C R-dependent control of cocaine-induced behavior is generally thought to be consequent to change of accumbal DA outflow (Filip and Cunningham, 2002;Fletcher et al, 2002Fletcher et al, , 2004Fletcher et al, , 2006Grottick et al, 2000;McMahon et al, 2001;Rocha et al, 2002). Although the present study was performed under different experimental procedures than previous behavioral studies (Filip and Cunningham, 2002;Fletcher et al, 2004;McMahon et al, 2001), it is tempting to consider a possible role of accumbal DA release in the 5-HT 2C R-dependent control of the behavioral effects of cocaine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, considering that the stimulant and reinforcing effects of cocaine depend in large part on elevated DA activity in the NAc (Di Chiara, 2002;Dunnett and Robbins, 1992), 5-HT 2C R-dependent control of cocaine-induced behavior is generally thought to be consequent to change of accumbal DA outflow (Filip and Cunningham, 2002;Fletcher et al, 2002Fletcher et al, , 2004Fletcher et al, , 2006Grottick et al, 2000;McMahon et al, 2001;Rocha et al, 2002). Although the present study was performed under different experimental procedures than previous behavioral studies (Filip and Cunningham, 2002;Fletcher et al, 2004;McMahon et al, 2001), it is tempting to consider a possible role of accumbal DA release in the 5-HT 2C R-dependent control of the behavioral effects of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…During recent years, numerous studies have focused on the role of the serotonergic2C receptor (5-HT 2C R) in the modulation of this DA pathway and its potential to control cocaine dependence (Bubar and Cunningham, 2006;Di Matteo et al, 2002;Higgins and Fletcher, 2003). Indeed, 5-HT 2C Rs are densely localized in brain regions containing DA cell bodies (VTA) and terminals (NAc) (Bubar and Cunningham, 2006;Clemett et al, 2000;Pazos et al, 1985;Pompeiano et al, 1994), and are known to modulate DA-dependent behavioral and neurochemical effects induced by cocaine (Fletcher et al, 2002(Fletcher et al, , 2006Grottick et al, 2000;McCreary and Cunningham, 1999;Navailles et al, 2004). Specifically, the systemic administration of the 5-HT 2C R agonist Ro 60-0175, and the 5-HT 2C R antagonist SB 242084 has been shown to respectively inhibit and potentiate cocaineinduced behaviors including its hypermotive and rewarding effects (Fletcher et al, 2002(Fletcher et al, , 2006Grottick et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that 5-HT can play a permissive or inhibitory role in the motor-activating effects of direct and indirect dopaminergic agonists by acting on different 5-HT receptor subtypes with 5-HT 2A and 5-HT 1B receptors being stimulatory and 5-HT 1C being inhibitory (Castanon et al, 2000;Fletcher et al, 2002Fletcher et al, , 2006Przegalinski et al, 2002;Bishop and Walker, 2003). Therefore, we investigated the possible ability of the 5-HT 2 receptor antagonist ritanserin (2 mg/kg) and the 5-HT 1B receptor antagonist GR 55562 (1 mg/kg) to counteract methamphetamine-and fluoxetine-induced potentiation of the locomotor activation induced by methylphenidate.…”
Section: Effect Of 5-ht Receptor Antagonists On Methamphetamine-and Fmentioning
confidence: 99%
“…Nevertheless, when dealing with specific 5-HT receptors, most studies demonstrate a facilitatory role of 5-HT 1B receptors on the biochemical, discriminative stimulus, motor, and rewarding effects of cocaine (Callahan and Cunningham, 1997;Lucas et al, 1997;Parsons et al, 1998;Castanon et al, 2000;Filip et al, 2001;Neumaier et al, 2002;Przegalinski et al, 2002;O'Dell and Parsons, 2004). The dampening effects of serotoninergic drugs on the behavioral effects of cocaine or other psychostimulants are most probably related to a predominant stimulation of receptors other than 5-HT 1B , such as 5-HT 2C (Fletcher et al, 2002(Fletcher et al, , 2006. Although the reasons why different 5-HT receptor subtypes are predominantly activated under different schedules of administration still need to be determined, 5-HT 1B receptors were the main 5-HT receptors involved in the results of the present study.…”
Section: Figurementioning
confidence: 99%